Experimental and numerical study on heat transfer enhancement in a channel with Z-shaped baffles - Sriromreun, Parkpoom; Thianpong, Chinaruk; Promvonge, Pongjet (My University, 2012)
The influence of baffle turbulators on heat transfer augmentation in a rectangular channel has been investigated experimentally and numerically. In the experiment, the baffles are placed in a zigzag shape (Z-shaped baffle) aligned in series on the isothermal-fluxed top wall, similar to the absorber plate of a solar air heater channel. The aim at using the Z-baffles is to create co-rotating vortex flows having a significant influence on the flow turbulence intensity leading to higher heat transfer enhancement in the tested channel. Effects of the Z-baffle height and pitch spacing length are examined to find the optimum thermal performance for the Reynolds number from 4400 to 20,400. The Z-baffles inclined to 45° relative to the main flow direction are characterized at three baffle- to channel-height ratios (e/. H= 0.1, 0.2 and 0.3) and baffle pitch ratios (P/. H= 1.5, 2 and 3). The experimental results show a significant effect of the presence of the Z-baffle on the heat transfer rate and friction loss over the smooth channel with no baffle. The Nusselt number, friction factor and thermal performance enhancement factor for the in-phase 45° Z-baffles are found to be considerably higher than those for the out-phase 45° Z-baffle at a similar operating condition. The in-phase 45° Z-baffle with larger e/. H provides higher heat transfer and friction loss than the one with smaller e/. H while the shorter pitch length yields the higher Nu, f and TEF than the larger one. The numerical work is also conducted to investigate the flow friction and heat transfer behaviors in the channel mounted with the 45° Z-baffles, and the numerical results are found in good agreement with experimental data. © 2012 Elsevier Ltd.
Keywords: Baffle; Heat transfer; Nusselt number; Turbulent channel flow; Vortex generator